Three-Dimensional Imaging of the Developing Vasculature within Stem Cell-Seeded Scaffolds Cultured in ovo - Woloszyk, Anna; Liccardo, Davide; Mitsiadis, Thimios A. (Frontiers in Physiology, 2016)
Successful tissue engineering requires functional vascularization of the three-dimensional constructs with the aim to serve as implants for tissue replacement and regeneration. The survival of the implant is only possible if the supply of oxygen and nutrients by developing capillaries from the host is established. The chorioallantoic membrane assay is a valuable tool to study the ingrowth and distribution of vessels into scaffolds composed by appropriate biomaterials and stem cell populations that are used in cell-based regenerative approaches. The developing vasculature of chicken embryos within cell-seeded scaffolds can be visualized with microcomputed tomography after intravenous injection of MicroFil®, which is a radiopaque contrast agent. Here, we provide a step-by-step protocol for the seeding of stem cells into silk fibroin scaffolds, the chorioallantoic membrane culture conditions, the procedure of MicroFil® perfusion, and finally the microcomputed tomography scanning. Three-dimensional imaging of the vascularized tissue engineered constructs provides an important analytical tool for studying the potential of cell seeded scaffolds to attract vessels and form vascular networks, as well as for analyzing the number, density, length, branching, and diameter of vessels. This in ovo method can greatly help to screen implants that will be used for tissue regeneration purposes before their in vivo testing, thereby reducing the amount of animals needed for pre-clinical studies.